UMP signed MoU with Rajarshi Shahu College of Engineering - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) and JSPM’s Rajarshi Shahu College of Engineering from Pune, India (JSPM’s RSCOE) signed a Memorandum of Understanding (MoU) that would enhance bilateral ties between the two institutes of higher learning.